2010
DOI: 10.1345/aph.1m719
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Community Pharmacists in Providing Clinical Medication Reviews

Abstract: The community pharmacists beneficially identified most DRPs and suggested many solutions. However, the assessment may underestimate the community pharmacists' abilities, as it relied on the records they kept and was based on a gold standard. While the pharmacists were self-selected, this study provides valuable insight into trained community pharmacists' clinical medication review performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
3
31
1
2
Order By: Relevance
“…Relatively little is known to what extent community pharmacists are able to identify DRPs in medication review . In particular, no research has been performed into the clinical relevance of these DRPs.…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Relatively little is known to what extent community pharmacists are able to identify DRPs in medication review . In particular, no research has been performed into the clinical relevance of these DRPs.…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…The number of DTPs (mean of 1.9) that pharmacists identified was toward the lower end of the range reported in prior studies, which have found 0.8 to 4.2 DTPs per patient annually. [16][17][18][19][20][21] However, the study population was taking a large number of medications and had a high prevalence of ADEs relative to the general US population. 22,23 In contrast to prior studies, pharmacists were required to meet with all study patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rare are the studies of the performance of the pharmacist within the framework of the analysis of drug prescriptions. Most foreigners are concerned with the community pharmacy exercise with the exception of only one [62][63][64][65][66]. One of them highlighted that the frequency of intervention could vary by a factor from one to ten from one pharmacist to another [64].…”
Section: Estimate the Practices Of Prescription Analysismentioning
confidence: 99%